2021
DOI: 10.1177/15347346211032046
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Complex Wounds by a Simple Skin Stretching System Associated With Vacuum Sealing Drainage—Clinical Outcome of 34 Patients

Abstract: Management of complex wounds with large skin defects presents a real challenge for orthopedic or reconstructive surgeons. We developed a simple skin stretching system associated with vacuum sealing drainage to examine the efficiency and complication. A total of 34 patients with different types of complex wounds were retrospectively included from January 2015 to March 2021. All patients in the study were underwent the treatment by 2 stages. The method was used to the wounds from 4.71 to 169.65 cm2 with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The combination of rubber bands and skin staples could also be used as a SSD [ 38 , 47 ]. The elastic bands from #7 surgical gloves may also be good choices [ 48 ]. Chen and Su reported a combination of a transfuser and nylon ligatures with a similar composition to ETEs [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The combination of rubber bands and skin staples could also be used as a SSD [ 38 , 47 ]. The elastic bands from #7 surgical gloves may also be good choices [ 48 ]. Chen and Su reported a combination of a transfuser and nylon ligatures with a similar composition to ETEs [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among all the studies included, 20 reported using the external tissue expansion technique in 209 patients undergoing fasciotomies. The application devices included a vessel loop [ 50–53 ], SureClosure® [ 54 ], Ty-raps [ 27 ], SBWCD [ 28 ], ETEs [ 29 , 55 ], Wisebands® [ 56 ], DermaClose® [ 57 ], TopClosure® [ 33 , 58 ], ABRA® [ 34 , 59 ], EASApprox® [ 60 ] and homemade devices [ 40 , 41 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations